Implication of Non-electrostatic Contribution to Deionization in Flow-Electrode CDI: Case Study of Nitrate Removal From Contaminated Source Waters - Song, Jingke; Ma, Jinxing; Zhang, Changyong; He, Calvin; Waite, T. David (Frontiers in Chemistry, 2019)
While flow-electrode capacitive deionization (FCDI) operated in short-circuited closed cycle (SCC) mode appears to hold promise for removal of salt from brackish source waters, there has been limited investigation of the removal of other water constituents such as nitrate, fluoride or bromide in combination with salt removal. Of particular concern is the effectiveness of FCDI when ions, such as nitrate, are recognized to non-electrostatically adsorb strongly to activated carbon particles thereby potentially rendering it difficult to regenerate these particles. In this study, SCC FCDI was used to desalt source waters containing nitrate at different concentrations. Results indicate that nitrate can be removed from source waters using FCDI to concentrations < 1 mg NO3-N L−1 though a lower quality target such as 10 mg L−1 would be more cost-effective, particularly where the influent nitrate concentration is high (50 mg NO3-N L−1). Although studies of the fate of nitrate in the FCDI system show that physico-chemical adsorption of nitrate to the carbon initially plays a vital role in nitrate removal, the ongoing process of nitrate removal is not significantly affected by this phenomenon with this lack of effect most likely due to the continued formation of electrical double layers enabling capacitive nitrate removal. In contrast to conventional CDI systems, constant voltage mode is shown to be more favorable in maintaining stable effluent quality in SCC FCDI because the decrease in electrical potential that occurs in constant current operation leads to a reduction in the extent of salt removal from the brackish source waters. Through periodic replacement of the electrolyte at a water recovery of 91.4%, we show that the FCDI system can achieve a continuous desalting performance with the effluent NO3-N concentration below 1 mg NO3-N L−1 at low energy consumption (~0.5 kWh m−3) but high productivity.